2020
DOI: 10.1212/nxi.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chains in MS

Abstract: ObjectiveThis cross-sectional study aims to assess the association between neuroaxonal damage assessed by serum neurofilament light chain (sNfL) and the Timed Up and Go (TUG)—a reliable and rapid measure of global neurologic disability—in patients with MS.MethodsA total of 41 consecutive patients with MS (38.0 ± 10.4 years; 57% women) with low level of disability (Expanded Disability Status Scale [EDSS] score 0–3) (EDSS score 1.0, interquartile range [IQR] 0.0–2.0) were included in this study. The TUG and sNfL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The relation between NfL and motor performance has been studied in MS (Allali et al, 2020), Parkinson disease (Aamodt et al, 2021;Ye et al, 2021) and in motoneuron disease, using Expanded Disability Status Scale, Unified Parkinson's Disease Rating Scale and ALS Functional Rating Scale-revised, respectively (Vacchiano et al, 2021). The TUG and gait speed tests are easy to perform, and our study confirms that they are sensitive tools to evaluate neurologic disability caused by neuroaxonal damage.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The relation between NfL and motor performance has been studied in MS (Allali et al, 2020), Parkinson disease (Aamodt et al, 2021;Ye et al, 2021) and in motoneuron disease, using Expanded Disability Status Scale, Unified Parkinson's Disease Rating Scale and ALS Functional Rating Scale-revised, respectively (Vacchiano et al, 2021). The TUG and gait speed tests are easy to perform, and our study confirms that they are sensitive tools to evaluate neurologic disability caused by neuroaxonal damage.…”
Section: Discussionsupporting
confidence: 71%
“…Most of these studies revealed an inverse relationship between general cognitive status and NfL level. Association between NfL and motor skills has been studied in MS, ALS and Parkinson disease (Allali et al, 2020;Vacchiano et al, 2021;Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%